2011
DOI: 10.1194/jlr.m011338
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells, macrophages, and crown-like structures distinguish subcutaneous from visceral fat in mice

Abstract: This article is available online at http://www.jlr.org is of grave consequence to human health. In fact, cardiovascular diseases, mostly as a result of long-standing metabolic dysregulations, are the leading cause of morbidity and mortality in many parts of the world.The pathogenesis of obesity-linked insulin resistance is only partially understood. Accumulating evidence has revealed a strong association between obesity-linked insulin resistance and infl ammation ( 2 ). Tumor necrosis factor-a (TNF-a ), a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
163
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 44 publications
9
163
0
2
Order By: Relevance
“…3b,c). Thus, the increase in protein density in eWAT of wild-type mice could potentially be explained by a massive macrophage infiltration 13,[18][19][20][21] . Obesity-induced macrophage infiltration into eWAT seemed to be lower in transgenic than in wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b,c). Thus, the increase in protein density in eWAT of wild-type mice could potentially be explained by a massive macrophage infiltration 13,[18][19][20][21] . Obesity-induced macrophage infiltration into eWAT seemed to be lower in transgenic than in wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, prolonged exposure to high-fat diet invokes hypertrophy-associated death of epididymal adipocytes 13 and shrinkage of the entire eWAT (Fig. 8, top-right mouse); the tissue is invaded with macrophages that both clean up dead adipocytes and release proinflammatory cytokines 13,20,21 . Consequently, the remaining adipocytes are severely damaged (as demonstrated by the absence of perilipin 1), are non-functional (incompetent to produce adiponectin) and insulin-resistant (Akt deficient), which contributes to the development of systemic insulin resistance and poor health.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mast cells in visceral fat of obese mice [15] and in human subcutaneous abdominal fat [2], suggests their role in the pathogenesis of obesity and insulin resistance and infl ammatory status [2,15]. Similarly ,in an adult prospective study examining the effect of fat distribution on asthma found that abdominal obesity was a risk factor for incident asthma in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, asthma has a higher prevalence in overweight and obese [14]. Obesity is accompanied by adipocyte death and accumulation of macrophages and mast cells in expanding adipose tissues [15]. Tryptases are serine peptidases highly abundant in granules of human and animal mast cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Epididymal adipose tissue (EAT) has been reported to be the most commonly used visceral fat depot in mouse studies, and its macrophage infiltration is most severe during the development of DIO [9]. In the lean state, EAT macrophages are mainly alternatively activated (M2) macrophages, which are characterised by CD206 and arginase 1.…”
Section: Introductionmentioning
confidence: 99%